Desenvolvimento de processamento por deformação multi-axial cíclica e avaliação do comportamento mecânico e evolução microestrutural do alumínio - Natanael Geraldo e Silva Almeida (2021)
The constant search for metals with outstanding mechanical behavior leads to the development of new processing techniques. Manufacturing processes that involve severe plastic deformation (SPD) have been widely used to improve the mechanical behavior of metals. These techniques promote the grain size refinement on a submicron scale in order to increase the metal strength. Among SPD techniques, MDF (Multi Directional Forging) stands out for the following advantages: (i) it is the only severe plastic deformation technique that allows the determination of the stress x strain curves for the material during processing, (ii); it is a simple processing technique that can be performed on any compression equipment, even without tools and (iii) it allows the processing of large samples. The methodologies adopted for MDF processing present some difficulties during processing due to geometric distortions caused by the friction between the material and the compression tools. These problems make it difficult to control the process. The alternatives to solve these problems increase the processing time and cost or change the strain path, and consequently the final properties of the processed material. This work aims to develop an MDF processing methodology that eliminates the current difficulties and to compare the results obtained by this methodology and the other methodologies that use the triaxial strain state, for the specific case of Aluminum processing. The developed methodology is efficient, decreases the processing time, is cheaper, maintains the triaxial strain state, and eliminates the main problems found in the literature's methodologies. The strain distribution, microhardness, and microstructural evolution point to a greater deformation in the central region of the samples when compared to the extremities.